HIV testing from an African Human Rights System perspective : an analysis of the legal and policy framework of Botswana, Ethiopia and Uganda - Sloth-Nielsen, Julia (University of Pretoria, 2008)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2007.